Exploring Cadets’ Perceptions of Challenges and Benefits in Gamified ESP Reading: A Case Study at a Maritime Academy - Amiruddin Hadi Wibowo; Akhmad Kasan Gupron; Eko Nugroho Widjatmoko; Romanda Annas Amrullah; Agus Dina Mirianto; Eva Rahmawati; Adams Ogirima Onivehu; Saifurahman Rohi (Scientia Publica Media, 2025)
English for Specific Purposes (ESP) is essential in maritime education, helping cadets with the language skills required to meet specific learning needs. However, traditional ESP reading instruction often lacks engagement and fails to motivate learners. In response, gamification, which integrates game design elements into learning environments, has emerged as a promising solution to enhance learner engagement and motivation. This study aims to explore cadets’ perceptions of the challenges and benefits of using gamification in ESP reading. The research was conducted using a qualitative case study approach at a maritime academy in East Java, Indonesia, involving 24 cadets. Participants were first-year students with intermediate English language proficiency. Data were collected through six sessions of gamified ESP reading lessons, semi-structured interviews, and participant observations. Thematic analysis was used to examine the cadets’ experiences, focusing on recurring themes related to motivation, learning outcomes, and technological challenges. The results showed that cadets generally expressed positive feelings about gamified ESP reading. They reported increased motivation and engagement due to game elements such as points, leaderboards, and real-time feedback, which made learning more interactive and enjoyable. However, challenges such as limited technological readiness, internet connectivity, and initial confusion with the game interface were also highlighted. Therefore, it can be concluded that gamification shows strong potential in enhancing cadets’ motivation and interest in ESP reading following the challenges and their constraints. These findings underscore the importance of integrating thoughtfully designed gamified strategies in maritime education to foster learner-centered and engaging ESP instruction.